Effect of season and sunlight on viral kinetics during hepatitis C virus therapy. Issue 1 (1st March 2017) - Hernández-Alvarez, Noemi; Pascasio Acevedo, Juan Manuel; Quintero, Enrique; Fernández Vázquez, Inmaculada; García-Eliz, María; de la Revilla Negro, Juan; Crespo García, Javier; Hernández-Guerra, Manuel
Abstract : Background and aims: Rapid viral response (RVR) during antiviral treatment for hepatitis C virus (HCV) predicts sustained viral response (SVR). Recently, vitamin D levels have been associated with SVR. As sunlight is the most important source of vitamin D and shows seasonal variation, we evaluated the effect of season on viral kinetics during peginterferon/ribavirin-based therapy for HCV. Methods: Consecutive HCV patients treated with peginterferon/ribavirin and boceprevir/ telaprevir (June 2011–July 2014) were included. Patients were grouped according to season when therapy was initiated (Season A: May–October and Season B: November–April) depending on hours of daily sunlight. Multiple logistic regression analysis included factors known to influence SVR to treatment. The dependent variables were undetectable viral load (VL) or VL ≤15 UI/mL (VL ≤15) at weeks 4, 8 and 12, end of treatment and SVR. Results: The study included 930 patients (66.8% men; median 54 years) treated with telaprevir (n=537) or boceprevir, without (n=481) or with lead-in therapy of peginterferon/ribavirin. Baseline characteristics of patients in Season A (45.3%, n=421) and Season B groups were similar. Overall, a higher rate of RVR (23.5% vs 16.1%, p=0.005) and VL ≤15 (51.0% vs 38.6%, p≤0.001) was observed in patients starting treatment during Season A versus Season B. By logistic regression analysis, initiating treatment in Season A proved to be an independent predictor of RVR and VL ≤15. Conclusions: In our setting, seasonality affects viral kinetics in HCV genotype 1 patients treated with peginterferon/ribavirin-based therapy. Our findings support the hypothesis that vitamin D influences viral response to peginterferon/ribavirin-based therapy.